Hot off the Press. Issue 8 (23rd July 2019) - Hill, Robert A.; Sutherland, Andrew
Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as peyssonnoside A from a Peyssonnelia species. Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as peyssonnoside A from a Peyssonnelia species.